2018
DOI: 10.2106/jbjs.rvw.17.00076
|View full text |Cite
|
Sign up to set email alerts
|

Abductor Tendon Tears of the Hip

Abstract: * The insertional anatomy of the hip abductors is fairly well established.* Magnetic resonance imaging remains the main diagnostic tool for these injuries, with the greatest specificity among various imaging technologies. In addition, it has utility in establishing a classification system that may have prognostic value.* There are multiple nonoperative and operative treatment modalities that have been shown to have satisfactory outcomes.* With the growing trend toward minimally invasive surgical procedures, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The hip abductors comprise the GMed, GMin and tensor fasciae latae. 4 The GMed originates from the anterior superior iliac spine and the outer border of the iliac crest towards the posterior superior iliac spine. 5 A recent cadaveric study demonstrated three distinct GMed origins: gluteal fossa and aponeurosis, and the posteroinferior edge of the iliac crest.…”
Section: Anatomy and Function Of Gluteal Musclesmentioning
confidence: 99%
See 3 more Smart Citations
“…The hip abductors comprise the GMed, GMin and tensor fasciae latae. 4 The GMed originates from the anterior superior iliac spine and the outer border of the iliac crest towards the posterior superior iliac spine. 5 A recent cadaveric study demonstrated three distinct GMed origins: gluteal fossa and aponeurosis, and the posteroinferior edge of the iliac crest.…”
Section: Anatomy and Function Of Gluteal Musclesmentioning
confidence: 99%
“…GTPS is more prevalent in women than men and demonstrates peak prevalence between the fourth and sixth decades of life. 4 The rate of gluteal tendinosis and ruptures increases with age. In an observational study of 185 patients over 50 years old with non-hip-related problems, the incidence of gluteal ruptures increased from 10% in the under the sixties to 50% in the over seventies groups.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“… 43 , 47 , 48 54 Gluteal tendinopathy typically affects women in their fourth to sixth decades of life and manifests as chronic lateral hip pain and tenderness. 45 , 47 The degenerative progression of tendinopathy is common. 3 , 13 The cellular mechanism of tendon degeneration has been described by Bhabra et al, 2 distinguishing 4 grades of tendinopathy ( Table 1 ).…”
mentioning
confidence: 99%